The Impact of Hormonal Changes in Elderly Women: A Literature Review - Helda, Helda; Latifah, Mira Maryani; Komalasari, Dini P.; Utami, Fenia; Rajab, Nurfadilah M.; Utami, Risa P.; Rahmadani, Sekar A.; Ramadhania, Shabrina A.; Stefani, Sheila (JURNAL INFO KESEHATAN, 2024)
As women age, hormonal changes become increasingly common and can significantly impact their overall health and well-being. In elderly women, these changes can lead to a range of physical and emotional symptoms that can greatly affect their quality of life. To further understand the health problems that arise from these hormonal changes, this study focused on menopause and andropause. The research methodology used in this study was a literature review. A total of 14 articles from PubMed, ScienceDirect, and PLOS One were reviewed, while established inclusion and exclusion criteria were taken into consideration. The findings suggest that a majority of postmenopausal women experience side effects from hormonal changes, including both physical and mental ailments. Menopause can also lead to sexual dysfunction, as well as an increased risk of osteoporosis, cardiovascular diseases, cancer, mental disorders, and chronic kidney disease. These changes can significantly impact an elderly individual's quality of life.